2017
DOI: 10.1103/physrevb.95.075113
|View full text |Cite
|
Sign up to set email alerts
|

Doppler cloak restores invisibility to objects in relativistic motion

Abstract: Although cloaks are effective at suppressing the observability of static objects, they can be defeated when in motion. Here we discuss a general technique to cloak the motion of objects from static observers, based on compensating the Doppler shift associated with their motion with frequency conversion sustained by a spatiotemporally modulated cover. The concept is theoretically and numerically demonstrated in a system composed of a planar reflector covered by a spatiotemporally modulated slab. It is shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…Dynamic modulation of metasurfaces adds a new dimensionality to the design space which can potentially overcome several limitations associated with the quasi‐static tunable metasurfaces. Furthermore, it can give rise to entirely novel functionalities such as Doppler cloaking, extreme energy accumulation, and nonreciprocal isolation and circulation . In order to realize time‐modulated metasurfaces, a high‐speed dynamic metasurface with continuous tunability is required such that its optical parameters can be modulated in time by applying a time‐varying biasing signal.…”
Section: Time‐modulated Metasurfacementioning
confidence: 99%
See 2 more Smart Citations
“…Dynamic modulation of metasurfaces adds a new dimensionality to the design space which can potentially overcome several limitations associated with the quasi‐static tunable metasurfaces. Furthermore, it can give rise to entirely novel functionalities such as Doppler cloaking, extreme energy accumulation, and nonreciprocal isolation and circulation . In order to realize time‐modulated metasurfaces, a high‐speed dynamic metasurface with continuous tunability is required such that its optical parameters can be modulated in time by applying a time‐varying biasing signal.…”
Section: Time‐modulated Metasurfacementioning
confidence: 99%
“…It is noteworthy that the pure frequency mixing in the time‐modulated metasurface mimics the Doppler shift of a moving object at the velocity of v = ( f 0 2 − ( f 0 + f m ) 2 ) c /( f 0 2 + ( f 0 + f m ) 2 ) with c being the velocity of light which leads to a velocity illusion. Moreover, the up‐ or downconversion of frequency can also be used to cancel out the Doppler shift of a moving object at this speed depending on its travelling direction realizing a Doppler cloak, that is, cloaking the motion from an stationary observer …”
Section: Time‐modulated Metasurfacementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we have shown that electronic components loading the antenna coating device may introduce even more degrees of freedom by tailoring the antenna response to the waveform. The antenna capabilities may be enriched even more through the use of cloaking devices integrating time-modulated metasurfaces [123], further paving the way to a new generation of intelligent antennas.…”
Section: Discussionmentioning
confidence: 99%
“…The research on time-varying electromagnetic platforms has a long history dating back to 1950s, when one of the early works, by Morgenthaler [17], explored theoretically what would happen to a monochromatic electromagnetic wave in a medium when the medium's phase velocity is rapidly changed in time. In the past decades, there have been numerous efforts in investigating various phenomena related to the temporal variation of electromagnetic media, providing temporal boundaries [18], temporal holography [19], Doppler cloaking [20], temporal band gaps [21][22][23], temporal effective medium concept [24], temporal impedance matching [25,26], Fresnel drag in spatiotemporal metamaterials [27], spacetime cloaks [28,29], modeling time and causality with metamaterials [30,31], rapidly growing plasma and accelerating reference frame [32], and exceptional points in timevarying media [33], just to name a few.…”
Section: Main Textmentioning
confidence: 99%